THE IMPACT OF AVAILABILITY BIAS AND REPRESENTATIVE BIAS ON INVESTMENT DECISIONS AND PERFORMANCE: THE ROLE OF FOMO AS AN INTERVENING VARIABLE - Nizar, Muhammad; Daljono, Daljono (Jurnal Apresiasi Ekonomi, 2024)
This research starts at the root of the problem of investor irrationality in the capital market. A series of studies in the last decade show that investors tend to behave irrationally, and phenomena or anomalies are repeatedly found in the capital market or financial markets that are not in line with standard/traditional finance theory or conventional/orthodox economics theory. This research aims to determine the impact of availability bias, representative bias, and fear of missing out (FOMO) on investment decisions and investment performance, and to find out that FOMO can act as a mediating variable between these relationships. The population in this study were all investors who traded in the Indonesian capital market through brokerage houses in several cities in Indonesia, and the sample size was 116 respondents, using a purposive sampling technique. The data used is primary data, data collection techniques use questionnaires. Structural Equation Modeling (SEM) data analysis technique with the SmartPLS analysis tool. The research results show that availability bias has a positive and significant impact on investment decisions and investment performance. Representative bias has a negative and insignificant impact on investment decisions, but representative bias has a positive and significant impact on investment performance. FOMO has a positive and significant impact on investment decisions and investment performance. Availability bias and representative bias have a positive and significant impact on FOMO. FOMO partially mediates the relationship between availability bias towards investment decisions and investment performance, then representative bias towards investment performance, but FOMO fully mediates the relationship between representative bias towards investment decisions. The results of this research would contribute to the development of knowledge about behavioral finance and have theoretical and policy implications for Indonesian retail investors.  Keywords: Availability Bias, Representative Bias, Fear of Missing Out (FOMO), Investment Decisions, and Investment Performance